Evolução hidrogeomorfológica de sistemas fluviais afetados por ruptura de barragem de rejeito - Juni Silveira Cordeiro (2022)
Changes in the hydrological cycle and in the contribution of sediments result in different responses of the fluvial system in the search for a new state of geomorphological equilibrium. When this contribution is the result of the collapse of a tailings dam, understanding the response of the fluvial system is essential for defining the strategies used to restore the impacted water courses. Thus, this research aimed to establish a methodology, based on the use of the Universal Soil Loss Equation (USLE), for the evaluation of the temporal evolution of marginal erosion and sediment dynamics of river systems, using as a reference the case study of the river system affected by the rupture of the Fundão Dam, Mariana (MG). The geomorphological characterizations and the evaluation of the hydrogeomorphological impacts triggered in this fluvial system were also sought. For this, the fluvial patterns were characterized through satellite images prior to the rupture event. The analysis of hydromorphological impacts was carried out through satellite images and field surveys. Soil loss estimation was performed using the USLE, while sediment transport assessment was performed using monitoring data from stations maintained by the National Water and Sanitation Agency, Minas Gerais Institute for Water Management and Renova Foundation. It was noted that the river system, before the Fundão Dam rupture, had meandering characteristics, with a tendency to evolve towards an intertwined pattern. The measures adopted to mitigate the impacts on the river system often proved to be inadequate, represented, for example, using rip rap on the convex edges of the meanders. Sensitivity analysis on images prior to the Fundão Dam failure, using different data and methodologies, allowed the definition of USLE factors. In this sensitivity analysis, about the erosivity factor, it was noted that the differences in mean values are much more affected by the selection of the erosivity equation than using data from satellite or complete rainfall historical series. As for the topographic factor, it was observed that a lower resolution of the digital elevation model (DEM) results in erosion rates 52% higher than those obtained with a higher-detailed DEM. Furthermore, the variation of the employed algorithm (map algebra, single stream, or multiple stream) results in average erosion values with differences of up to 91%. Thus, to evaluate the erosion rates necessary for this research, the topographic factor was obtained from a DEM with a resolution of 10 m, considering the multiple flow direction algorithm. The erosivity factor was determined using precipitation data from 62 rainfall stations located in the area delimited by the Rio Doce Hydrographic Basin. The soil map that includes the study area, prepared by the Federal University of Viçosa, together with the bibliography and information provided by the Renova Foundation, allowed the determination of the soil and tailings erodibility factor. The soil cover and conservation practices factors were obtained through the Normalized Difference Vegetation Index applied to 26 Landsat 8 satellite images. The highest erosion rate was identified in the satellite image that represents the scenario shortly after the rupture of the Fundão Dam, corresponding to an increase of about 23% when compared to the results obtained in the October 2015 image. However, the image obtained in June 2020, which depicts more current characteristics of this area, indicates a difference of little more than 1% of the erosion rate with respect to the scenario prior to the failure event. In tu rn, the assessment of the natural erosion potential indicates an increase of approximately 5% in the erosion rate after the Fundão Dam failure. Regarding the measurements associated with the transport of sediments, only one monitoring station maintained by the Renova Foundation has information related to the discharges of suspended sediments, bottom sediments and total solid, with data available only from October 2017. Considering this station of monitoring as an outlet of the hydrographic basin, it was noted that the erosion rate is 105 times greater than the total solid discharge determined for this station. In addition to adequate risk management associated with tailings disposal structures, the importance of soil and water planning and management is highlighted, aiming at the implementation of strategies to mitigate the effects of human actions on the environment.